2011
DOI: 10.4103/0971-9261.86864
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical pressure: A new prognostic indicator in congenital diaphragmatic hernia

Abstract: Aims:To evaluate the usefulness of intravesical pressure as a prognostic indicator in congenital diaphragmatic hernia.Material and Methods:In 25 cases, bladder pressure was measured intraoperatively during repair.Results:Cases were divided into three groups according to the intravesical pressure. Group 1: pressure <10 cm (n.9), Group 2: 10–15 cm (n.11) and Group 3: >15 cm (n.5). Number of ventilated days was tabulated against these groups. Median number of ventilated days for Group 1, with the lowest pressure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The mode of valve ablation in this study was valve ablation with Mohan's valvotome which has been shown to be effective method for valve ablation with comparable results to that achieved through endoscopy (16,18,19). This has proved to be valuable in our centre where facility for endoscopic ablation is unavailable.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The mode of valve ablation in this study was valve ablation with Mohan's valvotome which has been shown to be effective method for valve ablation with comparable results to that achieved through endoscopy (16,18,19). This has proved to be valuable in our centre where facility for endoscopic ablation is unavailable.…”
Section: Discussionmentioning
confidence: 87%
“…Mohan's valvotome have been found to be useful in valve ablation with comparable result with endoscopic valve ablation (16,18,19); Albeit, it may be associated with inadequacy of valve ablation (20) as the procedure is done blindly unlike endoscopic valve ablation which is usually performed under direct vision. In this study, there was failure of satisfactory ablation of valve in one of the patient which necessitated a repeat procedure.…”
Section: Challenges In Managementmentioning
confidence: 99%
“…have shown the use of measuring intravesical pressure as a prognostic marker in CDH. [ 6 ] There are other various indirect methods of measurement of IAP such as CVP and peak inspiratory pressure. Each of the methods has its own advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…IAP Measurement IAP was measured by intravesical manometry as described previously (13). The urinary bladder was emptied, and sterile normal saline was instilled into the bladder with a volume of 1 ml/kg.…”
Section: Patientsmentioning
confidence: 99%